Enhancing fatigue resistance of rib-to-floorbeam welded connections in orthotropic steel bridge decks by using UHPC layer: An experimental study. (February 2022) - Abdelbaset, Hesham; Cheng, Bin; Tian, Liang; Li, Hai-Ting; Zhao, Jian
Abstract: This study investigates the fatigue performance of rib-to-floorbeam welded connection in orthotropic steel decks (OSDs) reinforced by using ultra-high-performance concrete (UHPC) overlay. Three full-scale rib-to-floorbeam welded connections were fabricated and tested, one specimen represents the conventional OSD type, and the other two specimens represent the UHPC reinforced OSD type, so that the effect of employing UHPC layer can be explored. One rear axle load of HL-93 fatigue truck provided in AASHTO specifications was considered in the fatigue tests. The behaviors including fatigue crack initiation and propagation process, fatigue failure mode, characteristic fatigue life, and vertical rigidity degradation were all observed in the fatigue tests. Experimental results indicated that, under the effect of the same load amplitude, three cracks were observed for the unreinforced specimen, while only one crack for UHPC reinforced specimen was detected. It was observed that using UHPC overlay significantly extended the fatigue life of the rib-to-floorbeam welded connections, where the crack initiation life ( N 0 ) and through U-rib thickness fatigue life ( N 1 ) were increased by 236 % and 268 %, respectively, under the same load range. Moreover, vertical rigidity was significantly enhanced by employing UHPC layer, which could be due to the fact that the maximum rigidity degradation of the unreinforced and UHPC reinforced specimens were 25% and 14% under the effect of 0.64 and 1.64 million load cycles, respectively.